Doctors' experiences providing sexual and reproductive health care at Catholic Hospitals in the conflict-affected North-West region of Cameroon: a qualitative study - Adama Awasom-Fru; Maturin Désiré Sop Sop; Elin Charlotte Larsson; Sibylle Herzig van Wees (BMC, 2022)
Plain English Summary The main aim of this study was to explore doctors' experiences and perceptions of providing sexual and reproductive health care services at Catholic hospitals in a conflict affected area in Cameroon. In Cameroon, sexual, and reproductive health services are lacking, thereby contributing to a very high maternal mortality rate of about 456/100000 live births, far from the Sustainable Development Goal Agenda 2030. The Catholic Church remains one of the largest suppliers of health care services in Cameroon and receives huge funding from donors, but their role in providing sexual and reproductive health care is restricted by religious norms. This study therefore uses in-depth interviews with doctors from Catholic hospitals in the North-West region to explore their experiences in providing sexual and reproductive health services in a conflict region. Qualitative coding was done with NVivo, and data analysed using thematic analysis. The respondents described strict rules and a broad range of challenges to providing comprehensive sexual and reproductive health care services. Nonetheless, there is evidence of doctors overcoming obstacles to providing sexual and reproductive health (SRH) care despite the religious and political climate. However, while attempting to overcome challenges, participants describe numerous examples of poor SRH care and poor health outcomes. The study highlights the importance of understanding the intersect between religion and women's health, particularly in improving access to SRH for vulnerable populations in conflict affected areas. It further provides insight into doctors' motivations for practicing medicine, and how doctors cope and make efforts to provide care and minimize harm.